AL-QURâAN: TELAAH TUJUAN PENDIDIKAN - Arisanti, Kustiana (Humanistika : Jurnal Keislaman, 2017)
Â Abstract:Â Humans are born into the world to bring a set of physical organs and void mind and soul that sets it apart from other accordance, because humans equipped with a body, spirit, mind, mind, and lust. In order for the human component is run in accordance with nature, then human beings need to be trained to be qualified in accordance with the main purpose of its creation. Education is something that is absolutely to establish good personal, with intlektual and moral education. A good education is education that can include cognitive, affective and psychomotor, while promoting moral education. Quran as a guide to the teachings of Islam to be a first reference in shaping the individual Muslim who have good brain and good character. The Quran also offers a way and a perfect destination for educational ideal.Â Keywords: Quran, EducationÂ